2020
DOI: 10.3390/ijms21051632
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cerebral Blood Flow and Potential Neuroprotective Effect of Human Relaxin-2 (Serelaxin) During Hypoxia or Severe Hypovolemia in a Sheep Model

Abstract: Specific neuroprotective strategies to minimize cerebral damage caused by severe hypoxia or hypovolemia are lacking. Based on previous studies showing that relaxin-2/serelaxin increases cortical cerebral blood flow, we postulated that serelaxin might provide a neuroprotective effect. Therefore, we tested serelaxin in two emergency models: hypoxia was induced via inhalation of 5% oxygen and 95% nitrogen for 12 min; thereafter, the animals were reoxygenated. Hypovolemia was induced and maintained for 20 min by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Similar with other study, the cerebral blood oxygen decreased during the hypoxia [53]. Besides, our results showed that the cortical arteriovenous blood flow also decreased after hypoxia, which was consistent with René Schiffner et al's findings [54]. Ashley D. Harris' research found that across the grey matter, cerebral blood flow increased by approximately 15% over the course of hypoxia [55].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar with other study, the cerebral blood oxygen decreased during the hypoxia [53]. Besides, our results showed that the cortical arteriovenous blood flow also decreased after hypoxia, which was consistent with René Schiffner et al's findings [54]. Ashley D. Harris' research found that across the grey matter, cerebral blood flow increased by approximately 15% over the course of hypoxia [55].…”
Section: Discussionsupporting
confidence: 93%
“…Ashley D. Harris' research found that across the grey matter, cerebral blood flow increased by approximately 15% over the course of hypoxia [55]. But the latest study reported that the subcortical blood flow increased, whereas the cortical blood flow decreased in comparison to baseline values during hypoxia [54]. These findings suggest that there may be differences in cerebral blood flow response in different brain regions to hypoxia.…”
Section: Discussionmentioning
confidence: 96%